The aristotle approach to open hypermedia - Petrou, Costas; Martakos, Drakoulis; Hatzopoulos, Michael; Halamandaris, Stelios; Hadjiefthymiades, Stathes (Revista Colombiana de Computación, 2000)
Large-scale distributed hypermedia systems comprise a generation of powerful tools to meet the demands of the new information globalization era. The most promising of such systems have characteristics that allow for the easy adaptation both to an, actually, unpredictable technological evolution and to the constantly evolving information needs of users. Such systems are generally known as Open Hypermedia Systems (OHS). Recently, research effort has been focused on the formulation of a solid set of OHS standards (i.e., protocols, reference models and architectures) that would stem from a common understanding and thus, direct future implementations. Keywords: Open Hypermedia Systems, Hypermedia Modeling, Distributed Information Systems